Nanoscintillator-Mediated X-ray Inducible Photodynamic Therapy for In Vivo Cancer Treatment - Chen, Hongmin (Nano Lett, 2015)
Photodynamic therapy is a promising treatment method, but its applications are limited by the shallow penetration of visible light. Here, we report a novel X-ray inducible photodynamic therapy (X-PDT) approach that allows PDT to be regulated by X-rays. Upon X-ray irradiation, the integrated nanosystem, comprised of a core of a nanoscintillator and a mesoporous silica coating loaded with photosensitizers, converts X-ray photons to visible photons to activate the photosensitizers and cause efficient tumor shrinkage.